Molecular phylogeny and morphology reveal a new Cabalodontia species (Polyporales, Basidiomycota) from Yunnan Province, China - Su, Jiangqing; He, Min; Li, Qiqin; Dawa, Zhuoma; Shi, Yinmei; Zhao, Changlin (Charlie) (Phytotaxa, 2026)
The genus Cabalodontia belonging to the family Steccherinaceae, is an important member of wood-inhabiting fungi. In this study, one new species, Cabalodontia aurantiaca sp. nov. is collected from Yunnan, P.R. China, which is proposed based on a combination of morphological features and molecular evidence. This species C. aurantiaca is characterized by its orange basidiomata with odontoid hymenial surface, a monomitic hyphal system with clamped generative hyphae, thick-walled skeletocystidia and ellipsoid basidiospores (4–5 × 2.5–3.0 µm). Phylogenetic analysis of the new species is carried out based on the nuclear ribosomal internal transcribed spacer (ITS) and the nuclear large subunit (nLSU) of ribosomal DNA. The phylogenetic tree indicates that the new species belongs to the genus Cabalodontia, and it is retrieved as a sister to C. delicata. Full morphological description, illustrations, and phylogenetic analyses results for the new species are provided.